UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG BIJI MENGKUDUMorinda citrifolia L. MENGENDALIKAN ULAT PENGGEREK TONGKOL JAGUNG MANIS (Helicoverpa armigera Hubner) - Martina Martina; Hafiz fauzana (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Sweet corn crop (Zea mays saccaharata Sturt.) is the second food crop after rice. The main pest that attacks corn cobs and thus reduces production is Helicoverpa armigera. The control offered uses the noni (Morinda citrifolia L.) botanicalinsecticide. The aim of this study was to obtain a concentration of noni     (Morinda citrifolia L.) seed flour extract which was effective against the sweet corn cob borerHelicoverpa armigera. The research was conducted at the Plant Pest Laboratory, Faculty of Agriculture, Riau University. The research was conducted from June to August 2021. The study used a completely randomized design (CRD) consisting of five treatments and four replications in order to obtain 20 experimental units. The treatment used was the concentration of noni seed flour extract as follows: 0 g.l-1 water, 25 g.l-1 water, 50 g.l-1 water, 75 g.l-1 water, and 100 g.l-1 water. The parameters observed were the initial time of death, lethal time, daily mortality, total mortalityandchanges in behavior and morphology of larvae of Helicoverpa armigera. The results showed that the concentration of 100 g.l-1 water noni seed flour extract was able to control Helicoverpa armigera larvae with a total mortality of 72% but it was not yet effective in controlling Helicoverpaarmigera larvae because they had not been able to kill test insects of more or the same 80% at a maximum concentration of 10%.Key words :Morinda citrifolia L.,Helicoverpa armigera (Hubner), Botanical insecticide, concentration